الاستثمار السياحي في الجزائر بين الواقع والمأمول - تونسي, نجات; شخار, نعيمة (جامعة الوادي - University of Eloued, 2022)
لقد تم تسليط الضوء في هذه الورقة البحثية على الاستثمار السياحي في الجزائر كونه يعد من أهم البدائل المتاحة للنهوض بالاقتصاد الوطني، فقد تطرقنا إلى أهم دوافع الاستثمار في المجال السياحي، كما قمنا بعرض أهم المقومات السياحية التي تزخر بها الجزائر نظريا وبالأرقام. ولقد أسفرت هذه الدراسة على أن الجزائر وبالرغم من ما تملكه من مقومات سياحية تتيح لها أن تكون وجهة سياحية بامتياز، إلا أن القطاع السياحي فيها لم يلقى الدعم والاهتمام الكافيين للنهوض به وتطوير الاستثمار فيه وهذا بطبيعة الحال راجع إلى جملة من الأسباب حاولنا إبرازها، واقترحنا مجموعة من الحلول لتطوير هذا القطاع. This research paper highlighted tourism investment in Algeria as one of the most important alternatives available to promote the national economy, we discussed the most important motives for investment in tourism, and we also presented the most important tourism components that Algeria has in theory and in number. This study has resulted in Algeria, despite its tourism assets, allowing it to be a tourist destination with distinction, However, the tourism sector has not received sufficient support and attention for its promotion and investment development. This is, of course, due to a number of reasons that we have tried to highlight, and we have proposed a series of solutions for the development of this sector
Tourism investment in Algeria between reality and hope
مقال
Keywords: سياحة ; استثمار ;مقومات سياحية ; استثمار سياحي ; قطاع سياحي جزائري